Protokol STEMI yang dimodifikasi untuk PPCI selama Pandemi COVID-19: Apakah itu memperpanjang kinerja Door-To-Balloon - Putranto, Astri Yuniarsih; Putra, Teuku Muhammad Haykal; Soedarsono, Wahyu Aditya (Jurnal Kardiologi Indonesia, 2023)
Background COVID-19 became a main health problem and causes heavy impact, especially for healthcare system. Managing ST-Segment Elevation Myocardial Infarction (STEMI) patients before COVID-19 pandemic was already challenging enough for Healthcare Professionals (HCP) to pursue time-sensitive treatment. After COVID-19 pandemic, the time-sensitive treatment of pursuing door-to-balloon (DTB) time put a lot more burden to HCP. In this study, We sought to analyze how a change in protocol of PPCI in STEMI patients before and during the pandemic influence the performance of DTB in the hospital. Methods This is a single-centered retrospective observational study among STEMI patients which was treated by PPCI. Secondary data from the medical record were collected consecutively from April 2018 to January 2022 (46 months). We compared DTB performances before and during the pandemic. Result During 46 months period, the total population of this research was 880 patients. There were total 358 patients underwent PPCI before the pandemic and 522 patients after the pandemic. Modified protocol with the addition step to prevent the spread of COVID-19 had been implemented since April 2020. DTB increased significantly during the pandemic (90 (70-124) minutes vs 97 (76-135) minutes, p 0.002). The proportion of the patients who achieved DTB under 90 min was also significantly decreasing (56.4% vs 47.9%, p 0.0013). Conclusion It is necessary for PPCI center to modify PPCI workflow during the pandemic. A decent workflow should consider practicality and simplicity without compromising HCP and patient safety. Implementing modified PPCI workflow during the pandemic significantly increased DTB time but it is still within the limit of being reasonable and acceptable for the benefit of the patients.This article has a related Erratum.